Label-free multimodal non-linear optical imaging of three-dimensional cell cultures - Zhao, Wenying; Sun, Dingcheng; Yue, Shuhua (Frontiers in Physics, 2023)
3D cell cultures recapitulate tissue-specific diversity and better mimic the in vivo conditions compared to 2D cell cultures. Although confocal fluorescence microscopy is probably the most commonly used optical imaging technique to characterize 3D cell cultures, the limited imaging depth greatly hinders its application. Moreover, due to difficult diffusion of fluorescent probes into thick 3D cultures, the optical imaging techniques that rely on exogeneous fluorescent probes are not desirable. To address these problems, nonlinear optical (NLO) microscopy uses near infrared light excitation to achieve significant larger imaging depth and gains molecular selectivity in a label-free manner. Taking advantages of 3D optical sectioning capability, submicron resolution, and high speed, label-free multimodal NLO microscopy has offered great promise for regenerative medicine, tumor microenvironment research, and drug discovery. This article overviews and discusses the latest applications of label-free multimodal NLO microscopy as an emerging platform to facilitate 3D cell culture research.